Evaluating Extraction Methods for Caffeine Content in Gayo Arabica Coffee Oil through Gas Chromatography-Mass Spectroscopy - Khairan, Khairan; Musvira, Intan; Lala, Andi; Diah, Muhammad; Maulana, Aga; Idroes, Ghazi Mauer; Awang, Khalijah (Grimsa Journal of Science Engineering and Technology, 2024)
This study aims to determine physicochemical properties, and caffeine analysis of green bean coffee essential oil (GBCEO) and roasted bean coffee essential oil (RBCEO) by maceration and soxhlet extraction methods. The results indicated that RBCEO by maceration method have higher percentage of yield compared to GBCEO. By the same to soxhlet extraction method, RBCEO also showed higher percentage of yield compared to GBCEO. The refractive index of the GBCEOm and GBCEOs have a lower acid value compared to RBCEOm and RBCEOs. The specific gravity obtained for GBCEOm, RBCEOm, GBCEOs, and RBCEOs ranged from 0.87 to 0.97. The results showed that GBCEOm has the highest saponification value followed by RBCEOs. GBCEOm has the highest iodine value followed by RBCEOs, while RBCEOm and GBCEOs have a similar iodine value. The peroxide value showed that GBCEOs, and RBCEOs by soxhlet extraction method have higher peroxide value. The GC-MS analysis revealed that GBCEOm has higher caffeine followed by GBCEOs with the percentages area of 9.31% and 7.36% respectively. Meanwhile RBCEOm has lower caffeine followed by RBCEOs with the percentages area of 7.36% and 4.28% respectively. This finding showed that GBCEO shows higher caffeine compound compared with RBCEO.